A IMPLANTAÇÃO DO PROJETO TURÍSTICO ROTA DOS TROPEIROS (PR): POLÍTICAS PÚBLICAS E GOVERNANÇA” - Sahaidak, Alessandra (2013)
The abrangency of the touristic project “Rota dos Tropeiros (PR)” established a territory that involves sixteen districts disposed in the touristic zone of the Campos Gerais. The project aims to develop tourism based on the natural and cultural diversity of the region. It has on the tropeirismo its historical base, since it was a cycle that contributed with the economical and social development of the country and left material and immaterial marks along the way traveled by troupers. The region that the project reaches is an example of how some counties portrays part of the costumes and cultural inheritances of this period. Through the organization of the project the visitors find different segments of touristic activities, with options of itineraries for ecotourism, rural tourism, bicycle touring, cultural tourism, among others. To administrate and articulate the project, the Agencia de Desenvolvimento do Turismo nos Campos Gerais (ADTCG), acts attending to the municipalities and also the private initiative. The referred instance of governance attends to the project mainly on the divulgation and promotion of the destiny, through the elaboration of material and representation on events. The structuring by trainings, workshops and lectures are available to the counties and associates. Past few years of its release (2003), it sought to comprehend how the administration of the project through governance's instance happens. However, to understand the current command was necessary to study its organization and implantation. Established by public policies,the project, in consonance with the guiding objective of the national planning –decentralization – has as bias structuring the region’s potential, valuing the cultural,historical and natural features. This way, it was performed a research to have knowledge of how this project has been managed by an instance of governance. The theoretical basis was structured in territory concepts, public policies and tourism (touristic planning) as central axis, but also contemplated more specific themes, such as independent power of state, local power, decentralization and governance's instances.